Finding Dark Patterns in Casual Mobile Games Using Heuristic Evaluation - Dahlan, Refal Pradama; Susanty, Meredita (PETIR, 2022)
The popularity and monetary success of casual games are owed to many factors, but some of them that are not entirely honest and ethical. One of them comes in the form of the implementation of a dark pattern, a design pattern that negatively affects the experience of playing the game they are implemented. This research unveils the dark patterns most commonly used in popular and profitable casual mobile games, using heuristic evaluation conducted by five undergraduate student evaluators that have sufficient domain knowledge and experience of the topic at hand. Three of those dark patterns are (1) Pay to Skip:When the game sells various game elements that allow the players to skip some of its core challenges, (2) Grinding: When the game forces the players to sit through repetitive mechanics to make progress in the game, and (3) Playing by Appointment; When the game forces the player to play it during a specific time,through the use of rewards or punishments. The findings of this research should act as a counter-guideline on developing a casual game, as well as and provide the basis on future discussions on ethical game design.